Ewing Sarcoma with Ganglion Cells Post-Chemotherapy: A Case Report with Review of Literature - Dhandapani, Karthik; Gandhi, Jahnavi; Gami, Amisha (South Asian Journal of Cancer, 2023)
Ewing sarcoma arises in both bones (most common) and soft tissues and it commonly affects young adults. The tumor is composed of small round cells showing positivity for CD99 and FLI1 on immunohistochemistry (IHC). We describe ganglion cell differentiation post-chemotherapy in Ewing sarcoma which is a rare phenomenon.A 13-year-old girl presented with a chest wall mass. On biopsy correlating with IHC, the diagnosis was rendered as Ewing sarcoma. She underwent neoadjuvant chemotherapy followed by resection of the tumor. On microscopic evaluation, the tumor showed prominent ganglionic differentiation with expression of neuronal markers.Although maturation post-chemotherapy is an established finding with better prognosis in other primitive pediatric tumors, such neural differentiation is rare with only a few case reports in Ewing sarcoma both post- and pre-chemotherapy. Clinical significance and prognosis of such differentiation which appear to be better are not yet established and needs to be elucidated.
Keywords: Ewing sarcoma; ganglion cell; neural differentiation; chemotherapy; maturation